Differences of Indirect MAR Test in the Unexplained Infertile and Fertile Couples - Ramadhona, Nur Hafiz; Hinting, Aucky; Lunardhi, Hamdani (Folia Medica Indonesiana, 2020)
Infertility is the inability of a partner to get pregnant after regular sexual intercourse without contraception for 12 months. Based on the cause, male infertility is caused by genetic, hormonal, infectious, sexual, and unexplained infertility. However, many infertile couples are classified into unexplained infertility without an antisperm antibody (ASA) immunological examination. This study aimed to prove that couples classified as unexplained infertility can be caused by ASA wives. This was an observational study with a cross sectional study design. The sample consisted of 2 groups, in which the first group consisted of 36 fertile couples and the second group consisted of 35 unexplained infertility couples. All samples were carried out indirect MAR test to obtain the ASA value of the wife. If the wife's ASA value was >40%, the ASA results were positive. Conversely, if the ASA value was <40%, the ASA results were negative. From these 2 groups, there was a statistically significant difference (p<0.0001) that the wife's ASA value in the unexplained infertility group was significantly higher than that in the fertile group. This study concluded that the positive ASA results from the indirect MAR test were significantly found in the unexplained infertility sample.